META-ANALYSIS: TYPES OF MEDIA AND CHARACTERISTICS OF PHYSICAL MATERIALS SUITABLE FOR PHYSICS LEARNING MEDIA BASED ON ADOBE FLASH SOFTWARE - Azis, Hasbi; Risma, Mutia; Yolanda, Sinta; Desnita, Desnita; Usmeldi, Usmeldi (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
This research aimed to analyze the types of media and the characteristics of physics materials that are suitable for use in the development of physics learning media, using Adobe Flash software. The research uses a meta-analysis method, which is a method for analyzing many of the research that has been done. This research uses secondary data obtained from previous research in the form of journals related to the media using Adobe Flash software for senior high school physics subjects. The journals examined in this research consisted of 20 research articles that developed an adobe flash-based interactive learning media for physics learning in senior high schools. The number of articles reviewed consisted of 3 articles from international journals and 17 articles from national journals. Based on the results of the analysis that has been done, found 13 physics materials obtained from 20 journals analyzed, where the concepts of temperature, heat, and transfer are the most widely used material as content in the development of physics learning media based on Adobe Flash software. While the type of media that is widely used in computer-based learning media.